Efficacy and Mechanism of Mallotus furetianus Müll. Arg. Extract on Nonalcoholic Fatty Liver Disease. (28th April 2022) - Lin, Daobin; Ding, Yi; Cheng, Yabo; Chen, Yubin; Tang, Yunting; Wu, Xiaowen; Cheng, Yawei
Abstract : Nonalcoholic fatty liver disease (NAFLD) is currently the major cause of chronic liver disease globally. To observe the sedative effect of Mallotus furetianus extract (MFE) on NAFLD and the potential molecular mechanism, a high-fat diet (HFD) was used to induce NAFLD in rats for 8 weeks. Rats were orally given MFE (1.7 g/kg, 2.5 g/kg, and 3.3 g/kg) every day. Serum and liver biochemical indexes were detected. 16S rDNA sequencing was performed to test the changes in the gut microbiota. Mass spectrometry was used to analyze the changes in blood and liver metabolites and to perform a joint analysis of differential flora and differential metabolites. The results showed that MFE alleviated liver injury and decreased hepatic lipids content. ELISA analysis certificated that MFE reduced inflammation levels in rats fed with HFD. Compared to HFD rats with a normal diet, MFE significantly changed the overall structure of the intestinal flora and the composition of the intestinal microbes destroyed by HFD. In addition, MFE changes the metabolic levels of lipids and proteins in HFD rats. In conclusion, MFE effectively treated NAFLD and significantly improved the overall structure and intestinal microbial composition of the intestinal microbiota. The abundance of Bacteroides fragilis and Escherichia coli increased significantly in the partridge tea treatment group.